Multiple RFID doors control system - Syed Mohd Syukrizal, Ahmad Kori (2008)
These days the security system is an important part for a house or premise to avoid such incident like robbery. A lot of security systems types have been apply to make sure the safety of the premise. One of it is automatic identification system which really helpful human especially to identify the user ID (identification) of the premise. Radio Frequency Identification (RFID) is a component that suitable for this project. This project was designed and built the system using RFID for access the doors of the premise by indentify the RFID tag user. It then output their description such as ID numbers and user names to an attaches LCD screen. The system is powered by 9 V batteries or using AC TO DC adapter. The main idea in this project is to create a system which that can provide security for the safety of the premise. At the heart of project is a PIC 16F876A microcontroller will be used as a brain of the system that will control the system through a source code (C code) build using MPLab software. In this project, passive tag will be use as an identifier of the user. In the tag will be include RFID tag ID numbers of the user. Every RFID tag is unique because the ID of the tag is different for all the tag. So, it is really safe to use the RFID system for a premise security. Additionally, the PIC will process the data which receive from RFID tools and responsible for sending the output to the LCD screen which will be show the character.